Disseminated proliferative mesocestoidosis caused by Mesocestoides vogae (Cestoda: Cyclophyllidae) in a French bulldog in Japan - TOKIWA, Toshihiro; YOSHIMURA, Hisashi; TAKASE, Mami; KATO, Eigo; MORISAKI, Masateru; MORITA, Tatsushi; KOUTAKA, Mitsuru (Journal of Veterinary Medical Science, 2025)
This report describes a case of disseminated proliferative mesocestoidosis in a French bulldog from Aichi, Japan. In July 2023, the dog presented with chronic enteritis, and histological examination of the endoscopic biopsy specimen revealed parasites with suckers. Three months later, numerous tetrathyridia were detected in the inguinal mass. In April 2024, polymorphic tetrathyridia were detected on the visceral organs. These parasites were identified as Mesocestoides vogae (Cyclophylidea: Mesocestoididae) based on morphological features and sequence analyses. In Japan, M. vogae has only been reported in domestic dogs, with five cases of intestinal infection and one case of abdominal infection. This report is the first case of both intestinal and extraintestinal infections in the westernmost region of Japan.